2021
DOI: 10.3389/fonc.2021.625207
|View full text |Cite
|
Sign up to set email alerts
|

MYCN Drives a Tumor Immunosuppressive Environment Which Impacts Survival in Neuroblastoma

Abstract: A wide range of malignancies presents MYCN amplification (MNA) or dysregulation. MYCN is associated with poor prognosis and its over-expression leads to several dysregulations including metabolic reprogramming, mitochondria alteration, and cancer stem cell phenotype. Some hints suggest that MYCN overexpression leads to cancer immune-escape. However, this relationship presents various open questions. Our work investigated in details the relationship of MYCN with the immune system, finding a correlated immune-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 68 publications
0
31
0
Order By: Relevance
“…MYCN is a key driver of the disease and its overexpression reprograms neuroblastoma cells towards a stem-like phenotype that affects proliferation and cell growth, metabolism, and apoptosis inhibition. It also favors immune escape, invasion, and metastases [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…MYCN is a key driver of the disease and its overexpression reprograms neuroblastoma cells towards a stem-like phenotype that affects proliferation and cell growth, metabolism, and apoptosis inhibition. It also favors immune escape, invasion, and metastases [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lymphoid progenitor cells and B cells were also shown to play roles in the progression of other tumors (27,28). Higher levels of interferon (IFN)-γ-expressing CD4+ T (Th1) cells in patients with cancer have been associated with better prognosis, suggesting that Th1 cells are involved in controlling tumor regression (29)(30)(31). The elevated numbers of CD4 + Th1 T-cells in the high-risk group in the present study suggest that these cells do not play a protective role in NB.…”
Section: Discussionmentioning
confidence: 54%
“…Th1 cells polarize macrophages toward the M1 phenotype, whereas Th2 cells polarize macrophages toward the M2 phenotype. Evaluation of macrophage phenotype enrichment in NB showed that M1 macrophages are signi cantly enriched in NBs without MYCN ampli cation, whereas M2 macrophages are more abundant in NBs with MYCN ampli cation (31). CD56 NK cells are dysfunctional and prevalent in higher-stage tumors and correlate inversely with survival of melanoma patients (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…BGA002 showed a specific, dose-dependent decrease in the MYCN mRNA and protein, while decreasing the viability in a panel of 20 NB cell lines, followed by the block of different MYCN tumorigenic alterations, and to the anti-tumor efficacy of BGA002 in vivo in a MNA NB mouse model [ 55 ]. Moreover, while MYCN drives a tumor immunosuppressive environment, which impacts survival in several MYCN-positive tumors, the block of MYCN by the anti-MYCN BGA002 is able to reactivate and restore the effectiveness of the natural killer immune cells against NB [ 56 ]. It has been also found that BGA002 restores the retinoic acid (RA) response, leading to a differentiation or apoptosis in the MNA NB and also to a significant increase in survival in a mouse model of MNA-NB [ 57 ].…”
Section: Oligonucleotide Therapeutics As New Targeted Anti-cancer Dru...mentioning
confidence: 99%